2017
DOI: 10.1186/s12872-017-0661-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of therapy management and outcome in Takotsubo syndrome

Abstract: BackgroundTo date there is no validated evidence for standardized treatment of patients with Takotsubo syndrome (TTS). Medication therapy after final TTS diagnosis remains unclear. Previous data on patient outcome is ambivalent. Aim of this study was to evaluate medication therapy in TTS and to analyze patient outcome.MethodsWithin an observational retrospective cohort study we analyzed our medical records and included 72 patients with TTS that underwent cardiovascular magnetic resonance imaging (CMR) after a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 36 publications
0
30
0
2
Order By: Relevance
“…reported that treatment with antithrombotics and cardiac failure therapy within the first 2 months was achieved without the risk of bleeding and that the short‐term survival rate was high. They also reported that aspirin, oral anticoagulation, and low molecular weight heparin (among other therapies) were used for antithrombotic therapy . The selection of these medications was not clearly determined.…”
Section: Discussionmentioning
confidence: 99%
“…reported that treatment with antithrombotics and cardiac failure therapy within the first 2 months was achieved without the risk of bleeding and that the short‐term survival rate was high. They also reported that aspirin, oral anticoagulation, and low molecular weight heparin (among other therapies) were used for antithrombotic therapy . The selection of these medications was not clearly determined.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 4,313 articles were found of which 248 articles met the inclusion criteria. Based on predefined criteria, only 16 of these articles were included in this review ( Table 1) [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Literature Search and Data Sourcementioning
confidence: 99%
“…A Mayo clinic study failed to show any survival benefits of ACE inhibitors and beta-blockers in TTS patients [38]. An observation study by Abanador-Kamper et al reviewed all the treatment regimens for TTS patients and concluded that the benefits of heart failure cocktail medications and antithrombotic therapy is highest during the first two months of TTS, with a low side effect profile, high survival, and early recovery [11]. A case series study by Santoro et al concluded that the use of levosimendan can improve the LV ejection fraction and has a good safety profile [18].…”
Section: Tts With Complications -Heart Failurementioning
confidence: 99%
“…En ausencia de un consenso respecto a los criterios diagnósticos, en el año 2004, investigadores de la clínica Mayo propusieron cuatro criterios con el propósito de distinguir esta enfermedad de otras entidades como los SCA. Durante la fase aguda y subaguda, se pueden ver cambios electrocardiográficos como la elevación del ST, siendo este el más común (81 % de los casos), pero pueden verse otros cambios como inversión profunda de ondas T o prolongación del QT en las primeras 48 horas (4,22).…”
Section: Enfermedad De Takotsubounclassified
“…Las principales complicaciones son observadas en la primera fase de la enfermedad, que incluye: la insuficiencia cardiaca aguda, arritmias ventriculares, ruptura de la pared libre del ventrículo izquierdo y trombos intracavitarios. No hay evidencia relevante y actualizada para definir un manejo óptimo de la enfermedad, pero es claro que se debe evitar el uso de simpaticomiméticos, además de recomendarse el tratamiento con betabloqueadores cardioselectivos y uso de inhibidores de la enzima convertidora de angiotensina (IECAs) en los pacientes con disfunción ventricular persistente; si existe choque cardiogénico, se aconseja el uso de inotrópicos y dispositivos de asistencia ventricular (21,22).…”
Section: Enfermedad De Takotsubounclassified